New approach to bonding all-ceramic adhesive fixed partial dentures: A clinical report - (:unkn) unknown (MOSBY-ELSEVIER, 2002)
This clinical report describes the use of intraoral silica coating and silanization in an alternative bonding procedure for a 3-unit, all-ceramic, resin-bonded fixed partial denture.
Keywords: PORCELAIN SURFACE TREATMENTS; COMPOSITE RESIN; LUTING CEMENTS; STRENGTH; ETCHANTS; REPAIR; METAL